The current situation of Macau secondary multi-media teaching in physics - Ao, Wai Chi (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Curriculum development of MICE in tertiary education in Macao - Chan, Kam Lun (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Fashion education and the fashion industry in Macau linked through an NGO - Chan, Victoria Alexa Kuan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Moral values in education: a case study of one secondary school in Macau - Chen, Xin Wang (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An interpretative study of three aspects of teacher retention, turnover, and attrition in Macau - Cheong, Ngai Hong (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Changing minds: an analysis of the impact of the discovery learning methodologies on the student's attitude towards learning - Churchill, Geoffrey Raymond Alan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Macau school-based inquiry into shcool :industry links in science - Gull, Nausheen (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Realism philosophy and teachers' perceptions of teaching: some implications for school improvement in Macau - Gutierrez, Estrella Cruz (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Educational technology and the learning of history in a middle school in Macao - Lai, Su Kei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Community health specialist nurses and primary health care in Macao: Linking core competencies with curriculum development - Lam, Oi Ching Bernice Nogueira (University of Saint Joseph, 2012)
This study focuses on curriculum development for competency-based training of advanced practice nursing and smoking cessation in Macao. The aims of this thesis are: (a) to link the core competencies of Advanced Practice Nursing (APN) to curriculum development; (b) to make recommendations for improved specialist nurse training to address current problems of nursing; and (c) to gather data to indicate the scope and the severity of the issues related to nurse training in Macao. The thesis presents a comprehensive literature review of theoretical frameworks of competency-based nursing curricula, curriculum development and design, quality assurance, best practice in competency based models of nursing education, theories of change and innovation, needs analysis and stakeholder satisfaction. The thesis develops and implements a needs analysis and situational analysis of nursing education in Macao, using a „mixed methods‟ approach that integrates quantitative and qualitative data to identify the needs for, and perception of, core competencies in Community Health APNs by the health professionals and clients of the community. This includes an empirical survey of stakeholders, semi-structured interviews with professionals in the field of nursing and nurse training, structured questionnaires from clients, observational data on training and implementation of competency-based curricula, and evaluation of a piece of curriculum implementation of an APN training program on smoking cessation. Through action research cycles, the thesis synthesizes a range of literature and empirical data, and, from these, gains feedback for improvement and refinement of the new curriculum to be implemented. As well as conducting client satisfaction surveys of the primary health care provision and services in Macau and how these could be improved, the thesis provides the framework for a competency-based curriculum for nursing education in Macau. The thesis argues that, in order to keep abreast with current developments in nurse training and practice worldwide, it is essential for APN education and training to adopt a competency-based approach and for curricula to be framed in terms of competencies and outcomes. It indicates that these are currently under-developed in Macao, and that there is an urgent need for them to be addressed, in terms of general, core and specific competencies (e.g. smoking cessation). The thesis argues that, for such developments to iii happen, fundamental changes will be required to curricula and to APN nursing practice, as, even though there may be changes to curricula, the opportunity to put general and specific competencies into practice by APNs is currently severely restricted because of a range of constraints in Macao. The thesis argues that there is an urgent need for APNs to receive competency-based training and practice for smoking cessation, and the opportunity to put this training into practice. It indicates that even short workshops and training programs can be effective. The thesis argues that current obstacles to such practice can be identified, but that overcoming them presents serious challenges to the current system, and will require action on many fronts, including revisions to local legislation, nurse credentialing, facilitation by senior managers of the health service, and an increase in the supply of nurses. The thesis indicates that there is a strong and united will for changes to be made to bring about competency-based training, curricula and practice in Macao, but that there are many practical barriers to be overcome in order to bring about these changes
Keywords: Macao; PhD in Education (D-SE); Practice Nursing; School of Education. Education; Smoking Cessation; Thesis and Dissertations; University of Saint Joseph

Inclusive education in Macau: a dual teacher-parent perspective - Lam, Sao Lan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Motivation and factors affecting Japanese learning at the institute for tourism studies - Lao, Meng (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A school-based investigation of school disipline in Macau - Lei, Chi Hang (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Developing a community-based science curriculum for primary school students in Macau - Ng, Shuk Yan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A study of the factors affecting th retention of secondary English teachers in Macao private schools - Tai, Lai Kan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Teachers' perceptions of professional development: a case study of two schools in Macau - Wong, Fong Lei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Re-conceptualising computer literacy teaching and learning using constructivist principles and peer-tutoring - Wong, Kin Ming (University of Saint Joseph, 2015)
Nowadays, many university students (in Macau) are required to attend computer literacy courses to develop their basic skill levels and knowledge as part of their literacy foundation requirements. To be effective, such courses, which are very staff intensive and require access to expensive equipment and software, necessitate high levels of individual teaching. Evidence gathered at two study sites during this research, strongly suggests that many students may not be benefiting sufficiently from their computer literacy courses. Teachers frequently complain about the weak IT skills of many course graduates. This research proposes an innovative model for designing and delivering computer literacy courses based on constructivist principles, using peer-tutoring and blended learning to increase cost effectiveness and to improve student outcomes. Central to the model being proposed is the training and deployment of former course graduates as peer instructors and assessors. Constructivist principles provide a conceptual framework to ensure that the curriculum content, teaching strategies, learning styles and assessment procedures are properly aligned and fully understood by both the instructors and students to achieve high quality learning outcomes. An action research approach was used during the pilot and trail phases of the research to monitor the implementation of the model and evaluate its effectiveness using mixed methods. The planned two–phase action evaluation used a questionnaire to investigate the effectiveness of knowledge and skill transfer to students, and tutors’ learning progress; in-depth semi-structured interviews were used to survey, interpret and evaluate students’ and tutors’ perceptions of the new teaching and learning approach. Most respondents had a Confucian Heritage Cultural Background. For the first time, the research provides new insights into ways in which Confucian Heritage Cultural factors, interact with constructive principles in developing peer-tutoring methods in a university setting inMacau, and more widely
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph